The origin, persistence and failings of HIV/AIDS theory - Bauer, Henry H. (Jefferson, N.C. : McFarland & Co., 2007)
"This work challenges the belief that HIV is the cause of AIDS. Among the many topics explored are the failings of HIV testing, statistical evidence that HIV is not a sexually transmitted disease, and problems caused by the differing diagnostic criteria for AIDS around the world"--Provided by publisher.
Males and females -- Uniform trends -- False positives or contaminated samples? -- HIV is not an infection -- HIV discriminates by race -- What is it about race? -- Racism -- What do HIV tests detect? -- HIV and AIDS are not correlated -- AIDS -- Missteps in modern medical science -- How science progresses -- Research cartels and knowledge monopolies -- It's a virus -- Maintaining the monopoly -- The end of the beginning.
Includes bibliographical references (p. 251-274) and index.
Keywords: AIDS (Disease) -- Etiology; AIDS (Disease) -- Pathogenesis; HIV infections -- Pathogenesis; HIV (Viruses); HIV -- pathogenicity; HIV Infections; Acquired Immunodeficiency Syndrome -- etiology; Biomedical Research -- methods; Biomedical Research -- trends; Dissent and Disputes; Health Policy -- trends